1994
DOI: 10.1007/bf00932955
|View full text |Cite
|
Sign up to set email alerts
|

The behavior and pathogenicity ofToxacara canis larvae in mice of different strains

Abstract: In the present study the behavior and pathogenicity of second-stage larvae of Toxocara canis were examined in different mouse strains with special emphasis on the major histocompatibility complex (MHC). Mice of the inbred strains BALB, C3H, C57BL, and DBA and the outbred strain NMRI were infected orally with 1000 second-stage larvae of T. canis. The clinical behavior of the animals; the numbers of larvae detected in the liver, lungs, brain, and musculature; the hematological and serological parameters; and his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
2
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 11 publications
4
51
2
3
Order By: Relevance
“…Recently it was observed the presence of 3 rd stage larvae of T. canis in muscles of R. norvegicus from the 5 th at least the 60 th day after experimental infection with embryonated eggs of this ascarid and predominantly between the 10 th and the 30 th days after infection 10 , showing a migration larvae pattern similar of that found in other rodent species 1,8 ; corroborating the possibility of T. canis larval transference to carnivore animals by prey-predator relationship. On the other hand, there are some indications of muscle changes in humans infected by T. canis, resulting in the emergence of antistriational antibodies, suggesting the occurrence of anti-muscle autoimmune response 11 .…”
Section: Discussionsupporting
confidence: 63%
“…Recently it was observed the presence of 3 rd stage larvae of T. canis in muscles of R. norvegicus from the 5 th at least the 60 th day after experimental infection with embryonated eggs of this ascarid and predominantly between the 10 th and the 30 th days after infection 10 , showing a migration larvae pattern similar of that found in other rodent species 1,8 ; corroborating the possibility of T. canis larval transference to carnivore animals by prey-predator relationship. On the other hand, there are some indications of muscle changes in humans infected by T. canis, resulting in the emergence of antistriational antibodies, suggesting the occurrence of anti-muscle autoimmune response 11 .…”
Section: Discussionsupporting
confidence: 63%
“…Epe and colleagues infected four inbred strains of mice and one outbred strain and reported the presence of Toxocara larvae in the brains of all mice over the infection period, with the inbred BALB/c mice demonstrating the highest burdens (Epe et al, 1994). Investigating behaviour in inbred strains of mice is attractive as any infection-induced behavioural alterations that could be masked in heterogeneous outbred mice may appear more pronounced.…”
Section: The Toxocara Mouse Model: Brain Involvement Accumulation Anmentioning
confidence: 99%
“…BALB/c mice were selected as the susceptible strain and NIH mice were deemed to be resistant. The choice of strains was supported by previous studies where BALB/c mice have been reported to be more susceptible to T. canis infection (Bardón et al, 1994;Epe et al, 1994) and NIH mice demonstrated a higher resistance to T. canis infection than outbred CD1 mice (Abo-Shehada and Herbert, 1989). Recently, Kolbeková and colleagues demonstrated an accelerated speed of migration to the brain in re-infected BALB/c mice (Kolbeková et al, 2011).…”
Section: The Toxocara Mouse Model: Brain Involvement Accumulation Anmentioning
confidence: 99%
“…This results might indicate that somatic products released from the dead larvae are responsible for IgG1 production observed in the C3H strain. However, Epe et al (1994) examined the behaviour and pathogenicity of second-stage larva (L2) of T. canis in different mouse strains. The highest larval counts in the brain of all strains were found in BALB mice.…”
Section: Discussionmentioning
confidence: 99%